(untitled) (Mutah Journal of Humanities and Social Sciences (MJHSS), 2024)
The goal of this study is to identify the impact of internal work environment on occupational burnout in the Jordanian universities. The study population included public and private Jordanian universities, and the sample consisted of (259) faculty member in these universities. To achieve the goal of the study, the analytical descriptive method was used. The researcher designed an appropriate questionnaire which matched with the study goals. The statistical analysis employed arithmetic means, frequencies, percentages, linear and simple regression analyses, and the Cronbach’s alpha test. The research concluded that there is an impact of the components of the internal work environment collectively (organizational structure, organizational culture, information technology) on occupational burnout in Jordanian universities from the viewpoint of the faculty members, and it was found that there is a high level of agreement with the job burnout items. In light of the results, the researcher made a number of recommendations, the most prominent of which are the necessity of involving department directors at various levels in designing the organizational structure and formulating university strategies.